Effects of an Integrated Geriatric-Orthopedic Co-management (InGerO) on the Treatment of Older Orthopedic Patients with Native and Periprosthetic Joint Infections - De Bueck, Ulrike; Kohlhof, Hendrik; Wirtz, Dieter Christian; Lukas, Albert (Zeitschrift für Orthopädie und Unfallchirurgie, 2023)
In view of our aging society, co-management with a geriatrician is becoming increasingly important. While such collaborations have been working successfully in trauma surgery for years, it is still unclear whether they are also helpful for non-trauma patients in orthopedics. The aim of this study was to investigate the effect of such a cooperation in orthopedic non-trauma patients with native and periprosthetic joint infections on the basis of five key areas.A retrospective observational study as a before and after comparison was used to compare routine data from patients with and without orthogeriatric co-management after nontraumatic surgery. Eligible patients for the study were 70 years and older, had a diagnosis of hip, knee, or shoulder infection, and had been hospitalized for at least 14 days. Co-management consisted of close follow-up by a geriatrician, Comprehensive Geriatric Assessment, and “complex early geriatric rehabilitation”. The comparison group received therapy as usual, without a geriatrician and without “complex early geriatric rehabilitation”. Special attention was paid to delirium, pain, mobility, postoperative complications, and renal function.Analysis was carried out with 59 patients “with” and 63 “without” geriatric co-management. In the co-management group, delirium was detected significantly more often (p < 0.001), significantly lower pain intensities were measured at the time of discharge (p < 0.001), transfer ability had clearly improved more (p = 0.04), and renal function was more frequently noted (p = 0.04). No significant differences were found with respect to principal diagnoses, surgical procedures performed, complication rates, pressure ulcer and delirium incidence, operative revisions, or length of inpatient stay.Orthogeriatric co-management in orthopedic patients with native and periprosthetic joint infections and nontraumatic surgery appears to have positive impacts on recognition and treatment of delirium, pain management, transfer performance, and attention to renal function. Further studies should follow in order to conclusively assess the value of such co-management in orthopedic nontraumatic surgery patients.
Keywords: geriatric; orthopedic; co-management; non-trauma surgery; effects